2011
DOI: 10.1590/s1413-35552011000300006
|View full text |Cite
|
Sign up to set email alerts
|

Ativação muscular estabilizadora da patela e do quadril durante exercícios de agachamento em indivíduos saudáveis

Abstract: Background: Hip and knee muscle weaknesses have been associated with the onset of anterior knee pain (AKP). Therefore, the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Considering the abduction squatting after the exercises protocol, there was a significant VM RMS increase and a tendency for VL RMS increase, although not significant. Felicio et al 37 compared the myoelectric activation of patellar and pelvis stabilizers between the free and isometric thigh adduction and 6 Motriz, Rio Claro, v.26, Issue 1, 2020, e10190103 abduction squatting in healthy participants 37 . The results proved that the squatting associated with thigh abduction produced moderate and greater activations than those achieved with free squatting for the vastus medialis oblique, vastus lateralis oblique, vastus lateralis longus and gluteus medius muscles 37 .…”
Section: Discussionmentioning
confidence: 99%
“…Considering the abduction squatting after the exercises protocol, there was a significant VM RMS increase and a tendency for VL RMS increase, although not significant. Felicio et al 37 compared the myoelectric activation of patellar and pelvis stabilizers between the free and isometric thigh adduction and 6 Motriz, Rio Claro, v.26, Issue 1, 2020, e10190103 abduction squatting in healthy participants 37 . The results proved that the squatting associated with thigh abduction produced moderate and greater activations than those achieved with free squatting for the vastus medialis oblique, vastus lateralis oblique, vastus lateralis longus and gluteus medius muscles 37 .…”
Section: Discussionmentioning
confidence: 99%
“…If these muscles are weakened, the lower limbs are improperly positioned. There is no description in the literature regarding the most efficient way to perform squat exercises in order to promote balanced activation of the dynamic stabilizers of the patella and higher electrical activity of the pelvic stabilizers [24]. Furthermore, there is no information in the available literature to allow authors to select the parameters used for the division into phases.…”
Section: Kinematics and Kinetics Parametersmentioning
confidence: 99%
“…[17][18][19] Among the squat exercises, Felício et al 20 verified that the squat combined with hip adduction yields greater electrical activation of the vastus medialis oblique. Oppositely, Gramani-Say et al 21 , Bevilaqua-Grossi et al 18 and Tang et al 16 found bigger activation of the VM during squat performed at 60° of knee flexion when compared to a 45° of knee flexion.…”
mentioning
confidence: 99%
“…Although some authors suggest that CKC, such as squat, can be safer for patients with PFPS, since they provide dynamic stabilization of the joint, causing a closer relation between the activations levels of VM and VL, 20,30 and that studies like Fehr et al 31 consider that CKC is more efficient for improving functionality when compared to OKC exercises, Escamilla 32 emphasizes that the squat is a functional activity which bears complaints among the patients with PFPS, and Escamilla et al 33 concluded that the OKC produce lower compressive forces when compared to CKC, which generates bigger compressive forces, especially in angles above 85°.…”
mentioning
confidence: 99%
See 1 more Smart Citation